Investigation of the presence of elements of performance management in the generation of organizational learning: a case study - Sandra Mara Iesbik Valmorbida; Sandra Rolim Ensslin (Revista Catarinense da Ciência Contábil, 2020)
This research investigated the presence of the elements of Performance Management (PM) in the generation of Organizational Learning, through the perception of stakeholders in the process. It is a case study, with interviews of three people directly involved with the design, implementation, use and feedback of the system. The semi-structured interviews were guided by the basic literature that points out the presence of the elements. Analyzing the speeches of the interviewees, it appears that the PM system was built in a continuous cycle of reflection, since previous strategic planning experiences did not prosper. From the interviewees' perception, the system enabled the organization to become aware of reality, detect and correct existing and, previously, unknown problems. Thus, it is possible to think of improvement actions. In addition, it was evident that communication permeated the entire process of PM, because it explained what was desired with the construction of metrics and directed the goal setting. These, encouraged the use of information for management and guaranteed timely feedback, allowing the comparison of the results obtained with those expected, defined by the goals set. This feedback provided the participation of all stakeholders, making it possible for the organization to verify the achievement of its strategic objectives, periodically feedback the system, reviewing its strategy, and reviewing its beliefs, behaviors and actions, making the organization more prepared for environmental changes. Finally, it can be concluded that learning is perceived by managers when they are able to show what the organization wanted to achieve, reflect on the adequacy of the objectives pursued and demonstrate that collaboration occurs in improving routines already developed in the organization. Also, when they are able to identify what is important to measure, parameterize the goals with these data, and provide feedback, in a way that makes it possible to analyze the results, comparing them with the established goals. And above all, when it is possible to trust information to guide decisions.